Design and Build Platform E-Commerce at TUTUS BETTA FARM: Rancang Bangun Platform E-Commerce pada TUTUS BETTA FARM - Bachtiar, Alief; Firliana, Rina; Harini, Dwi (Universitas Nusantara PGRI Kediri, 2024)
E-Commerce is one of the areas that has undergone great progress as a result of the rapid growth of information and communication technology since the advent of the Internet. E-Commerce facilitates the online shopping process and provides convenience and efficiency to customers. TUTUS BETTA FARM, a shrimp farmer located in Kediri district, has had difficulty using an e-commerce platform to improve the accessibility and efficiency of their business. Problems identified include difficulties in accessing physical stores by buyers, manual ordering, and limited payment options. The proposed solution is the development of a web-based E-Commerce platform using React Js and Next Js, as well as the integration of the Midtrans payment gateway to facilitate online payments.